Splenic lipidosis after administration of intravenous fat emulsions. - Forbes, G B (1978)
Spleens showing fatty infiltration and necrosis of the pulp were found at necropsy on several patients who had received intravenous fat emulsions during their terminal illnesses. The postmortem findings are described and the clinicopathological correlation is discussed with special reference to the phenomenon of creaming of the emulsion.